Prescription profile of antihypertensive medications in Primary Care in the city of Araranguá (Research, Society and Development, 2022)
High Blood Pressure is a disease of extreme recurrence in the brazilian population and presents characteristics that make it an important risk factor for the development of cardiovascular outcomes. In this context, the study of the prescriptive profile of drugs in a given location can identify and assess important variables in prescriptive quality. This study analyzed the profile of prescription of antihypertensive drugs in Primary Care in the town of Araranguá, in Santa Catarina state, according to the perception of prescribers. A cross-sectional, quantitative, descriptive study was carried out through a semi-structured interview, applied between December 2021 and February 2022. The study population consisted of medical prescribers who work in the Primary Care network in the town of Araranguá. The obtained results showed that the profile of the physicians is composed, predominantly, of young professionals (